Effects Of Ragging On Students Across Multiple Disciplines In A Medical University - Basharat, Muhammad Abdullah; Rehman, Tanzeel Ur; Hamza, Hafiz Muhammad; Riaz, Mehwish; Ali, Saad (Journal of Rawalpindi Medical College, 2025)
Objective: This cross-sectional study aims to assess the perception of ragging and its effects on first-year students across various departments, including MBBS, Dentistry (BDS), Physiotherapy (DPT), and Nursing (BSN). Methods: A total of 293 students from four departments (MBBS, BDS, DPT, and BSN) participated in this study. Data was collected using a self-structured questionnaire, covering perceptions of ragging, mental health impacts, physical and verbal abuse, academic consequences, and anti-ragging policies. Chi-Square tests were applied to analyse associations between ragging experiences and gender, between physical and verbal abuse, and between reporting of such practices and policies against them. Chi-square analysis between gender and the academic impacts of ragging showed different score distributions among males and females. Results: The results revealed that 94.5% of students reported experiencing ragging (Figure 1), with 46.7% viewing it as a highly negative experience. Significant impacts on mental health were reported, including upsetting memories (35%) and suicidal thoughts (6.5%). Physical and verbal abuse were prevalent, affecting 16.6% and 43% of students, respectively. Gender analysis showed significant differences in academic impact (p = 0.025), physical and verbal abuse (p = 0.021), and reporting practices (p = 0.034). Departmental analysis also showed significant variation, with Physiotherapy students reporting the highest prevalence of negative experiences (p = 0.00001) (Table 4). Only 17.3% of students lodged formal complaints, and 58.5% found anti-ragging policies ineffective. Conclusion: This study highlights the pervasive nature of ragging and its detrimental effects on students’ mental health and academic performance, emphasising the need for more stringent anti-ragging measures across departments.